Current state of hematopoietic cell transplantation in CLL as smart therapies emerge. Issue 1 (March 2016) - Kharfan-Dabaja, Mohamed A.; El-Asmar, Jessica; Awan, Farrukh T.; Hamadani, Mehdi; Ayala, Ernesto
Abstract: Novel therapies targeting various kinases downstream of the B-cell receptor have emerged along with monoclonal antibodies and BCL-2 antagonists, and are changing the therapeutic landscape of chronic lymphocytic leukemia. However, cure remains unattainable unless eligible patients are offered an allogeneic hematopoietic cell transplant. Access to allogeneic hematopoietic cell transplantation has expanded considerably with availability of reduced intensity conditioning regimens which is capable offering durable remissions even in poor-risk disease. Encouraging data from ibrutinib and venetoclax in Del17p is challenging the notion of disease eradication as the ultimate therapeutic goal to a new concept of merely disease control. By favoring the non-transplant approach, patients should be aware that there are no established salvage therapies, yet, to rescue disease progression after ibrutinib. When disease eradication is the desirable approach, a reduced intensity conditioning allogeneic hematopoietic cell transplant is the preferred choice at this time.